Monitoring of deforestation and urban occupation through the analysis of NDVI and NDBI indices in the municipality of Paraíso das Águas/MS - Cabreira , Ygor Flávio dos Santos; Freitas , Gabriela Zacalusni; Guaraldo , Eliane (Seven Editora, 2023)
This study takes in consideration one of the toughest environmental challenges we face nowadays, the deforestation. Studies on environmental control and analysis through remote sensing have already permeated the academic fields, the more information we have, the better our chances to fight outbreaks of deforestation and to preserve the native vegetation cover of a region are. Paraíso das Águas/ Mato Grosso do Sul is in the Cerrado, one of the Brazilian biomes most afflicted by deforestation, therefore, georeferencing was the tool used to monitor the problem, through the avaliation of the indices of Normalized Difference Vegetation Index (NDVI) and Normalized Difference Built-Up Index (NDBI), so that this information can be used in the future to control and orientate the process of urban and sustainable growth and Development of the municipality. Our data highlight that the most deforestation in the municipality is to open spaces for farming, which underscores the fact that these activities require a more rigorous and adequate local environment control, taking in consideration that this is their largest source of income. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-103